English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-12-12 14:19:03 · 9 answers · asked by natewat99 2 in Science & Mathematics Mathematics

9 answers

3/ (1-root 2) * (1+ root 2)/ (1+ root 2)
3*(1+root 2) / ((1-root 2)*(1+root 2))
(3+ 3root 2) / (1- 2)
(3+ 3 root 2) / -1
-3 - 3 root 2
solved!!!!

2006-12-12 14:22:59 · answer #1 · answered by fortman 3 · 1 0

You need to rationalize the denominator by multiplying by the conjugate.

Multiply the numerator and the denominator by 1 +root 2

This will give 3(1 + root 2) in the numerator to simplify to 3 + 3 root2

The denominator expands using FOIL to get: 1 + root2 - root2 - 2
which reduces to 1 - 2 = -1

Dividing the numerator by the denominator gives -3 - 3root.

2006-12-12 14:24:09 · answer #2 · answered by keely_66 3 · 1 0

Rationalize the denominator by multiplying both the numerator and denominator by the denominator yet with the different signal (a million - ?3) and foiling it out. note how both surds cancel one yet another out: 2(a million - ?3) = 2 - 2?3 (a million + ?3)(a million - ?3) = a million - ?3 + ?3 - 3 = a million - 3 = -2 As a fragment: (2 - 2?3) / (-2) Simplify the fraction: -a million + ?3

2016-11-26 00:01:48 · answer #3 · answered by ? 4 · 0 0

PEACE BE UPON YOU

Q: Simplify: 3 / (1 - root 2)?

ANS:-
IT IS IN THE SURD FORM IN CANT BE SIMPLIFIED MORE
OR IF ITS NOT NESSESSARLY TO HAVE IT IN SURD FORM WRIYE THIS ANSWER -7.242640687 AND IT COUNT BE SIMPLYFIED MORE

I WISH I ANSWERE IN THE WAY YOU PREFARED AND (SORRY) LARGNESS IF I MISUNDERSTOD YOUR QUESTION

2006-12-12 14:27:33 · answer #4 · answered by Anonymous · 0 1

3/(1 - sqrt(2))

Multiply top and bottom by (1 + sqrt(2))

(3(1 + sqrt(2)))/((1 - sqrt(2))(1 + sqrt(2))
(3(1 + sqrt(2)))/(1 + sqrt(2) - sqrt(2) - 2)
(3(1 + sqrt(2)))/(1 - 2)
(3(1 + sqrt(2)))/(-1)

ANS : -3 - 3sqrt(2) or -3(1 + sqrt(2))

2006-12-12 15:22:27 · answer #5 · answered by Sherman81 6 · 0 0

-3(sqrt(2) + 1) and that equals -7.242640687

2006-12-12 14:24:22 · answer #6 · answered by Anonymous · 0 1

3/(1-rt 2)
multiply numerator and deminator by conjugate ...
so conjugate of (1- rt 2) is (1+ rt 2)
so,
3/(1-rt2) = [3 * (1+ rt2)]/ [(1- rt 2)(1+ rt2)]
[(i.e)(a+b)(a-b) = a^2 -b^2 ] , value of rt 2 = 1.414
= [3 + 3 rt 2] / [1-2]
= [3 + (3*1.414)] / [-1]
= [3+ 4.242]/[-1]
= [7.242]/[-1]
3/(1-rt2) = - 7.242

2006-12-12 14:35:42 · answer #7 · answered by latha 2 · 0 1

3/(1-sqrt2)
= 3/(1-sqrt2) x (1+sqrt2)/(1+sqrt2)
= 3(1+sqrt2)/(1-2)
= -3(1+sqrt2)

Note: (a+b)(a-b) = a^2 - b^2

2006-12-13 13:50:37 · answer #8 · answered by Kemmy 6 · 0 0

multiply through by conjugate
(1+root2)
3/(1-root2)
=3(1+root2)/(1-root2)(1+root2)
=3(1+root2)/(1-2)
=(-3)(1+root2)
= -7.242640687

i hope that this helps

2006-12-12 15:39:17 · answer #9 · answered by Anonymous · 0 1

fedest.com, questions and answers